You wouldn't want to be a medieval knight! : armor you'd rather not wear - Macdonald, Fiona, 1958-; Antram, David, 1958-; Salariya, David (New York : Franklin Watts, 2004)
Provides information on the training, traditions, and life of knights during the Middle Ages for a young boy who thinks that that is what he wants to be.
Glamorous knights -- Do you have a rich, noble family? -- Time to start training -- Loyalty to your lord -- Life in a castle -- Get geared up -- Armed and dangerous -- Coping on crusade -- Surviving a siege -- Bravery in battle -- Don't fall off your horse! -- So many ways to die.
Includes index.
Keywords: Knights and knighthood -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Knights and knighthood; Civilization, Medieval